PERSEPSI PELAKU USAHA TERHADAP RETURN BANK KONVENSIONAL DALAM EKOSISTEM KEUANGAN SYARIAH DI ACEH: PERSEPSI PELAKU USAHA TERHADAP RETURN BANK KONVENSIONAL DALAM EKOSISTEM KEUANGAN SYARIAH DI ACEH - Cut Nova Rianda; Mukhsinuddin (An Nuqud Journal of Islamic Economics, 2025)
The implementation of the Qanun on Sharia Financial Institutions (LKS) in Aceh since 2022 has made Aceh the only province in Indonesia that requires a comprehensive Islamic financial system. However, limited financial services, infrastructure and business needs have led to a push to bring back conventional bank services. This article aims to examine the perceptions of businesses towards the reintroduction of conventional banks in the framework of fulfilling financial services in three districts: Nagan Raya, Aceh Barat Daya, and Aceh Jaya. This research uses a qualitative approach with in-depth interviews with business actors and stakeholders. The results show an ambivalence in perceptions: on the one hand, businesses value sharia principles; on the other hand, they need flexibility, speed, and adequate access to credit as offered by conventional banks. Policy implications indicate the need for harmonisation of financial services that are adaptive to the needs of the local economy without neglecting the spirit of sharia.